DAMPAK PELATIHAN ONLINE RESCHEDULE LIFESTYLE PASIEN HIPERTENSI TERHADAP PENINGKATAN PENGETAHUAN DAN KEMAMPUAN NERS FRESH GRADUATE DI MASA PANDEMI COVID -19 - Windu Santoso; Sri Sudarsih (Universitas Islam Negeri Alauddin Makassar, 2021)
The high mortality rate in hypertensive sufferers is one sign that the Indonesian people still do not understand the importance of adherence to medication and lifestyle changes. The purpose of this study was to determine the effect of online training on lifestyle rescheduling of hypertensive patients on the knowledge and abilities of fresh graduate nurses. The research design used a quasi-experimental pre-test post-test with a population of all Fresh Graduate Stikes Bina Sehat PPNI Mojokerto. The sample used was 30 respondents using simple random sampling. Data collection using a questionnaire. Data analysis was carried out with frequency distribution and then performed normality test using Kolmogorov Smirnoff to obtain data for the two normal variables. To determine the impact of online training on knowledge and abilities, the Paired t-test was conducted. Based on the results of the Paired T-Test on the impact of online training on knowledge, the value of p = 0.000 <0.05 was obtained and the results of the Paired T-Test on the impact of online training on ability obtained p-value = 0.001 <0.05. The results of the study prove that online training on Lifestyle Rescheduling has an impact on increasing the knowledge and abilities of respondents. Training in the form of interactive sessions and the use of various presentation methods and assistance in the application of lifestyle rescheduling of hypertensive patients can increase the knowledge and abilities of respondents.